Mn-single-atom nano-multizyme enabled NIR-II photoacoustically monitored, photothermally enhanced ROS storm for combined cancer therapy - Wang, Xiaozhe (2024)
Rationale: To realize imaging-guided multi-modality cancer therapy with minimal side effects remains highly challenging. Methods: We devised a bioinspired hollow nitrogen-doped carbon sphere anchored with individually dispersed Mn atoms (Mn/N-HCN) via oxidation polymerization with triton micelle as a soft template, followed by carbonization and annealing. Enzyme kinetic analysis and optical properties were performed to evaluate the imaging-guided photothermally synergized nanocatalytic therapy. Results: Simultaneously mimicking several natural enzymes, namely peroxidase (POD), catalase (CAT), oxidase (OXD), and glutathione peroxidase (GPx), this nano-multizyme is able to produce highly cytotoxic hydroxyl radical (•OH) and singlet oxygen (1 O2) without external energy input through parallel and series catalytic reactions and suppress the upregulated antioxidant (glutathione) in tumor. Furthermore, NIR-II absorbing Mn/N-HCN permits photothermal therapy (PTT), enhancement of CAT activity, and photoacoustic (PA) imaging to monitor the accumulation kinetics of the nanozyme and catalytic process in situ. Both in vitro and in vivo experiments demonstrate that near-infraredII (NIR-II) PA-imaging guided, photothermally enhanced and synergized nanocatalytic therapy is effcient to induce apoptosis of cancerous cells and eradicate tumor tissue. Conclusions: This study not only demonstrates a new method for effective cancer diagnosis and therapy but also provides new insights into designing multi-functional nanozymes.